2019
DOI: 10.1002/uog.20284
|View full text |Cite
|
Sign up to set email alerts
|

Screening for trisomies by cfDNA testing of maternal blood in twin pregnancy: update of The Fetal Medicine Foundation results and meta‐analysis

Abstract: Objectives To report on the routine clinical implementation of cell-free DNA (cfDNA) analysis of maternal blood for trisomies 21, 18 and 13 in twin pregnancy and to define the performance of the test by combining our results with those identified in a systematic review of the literature. MethodsThe data for the prospective study were derived from screening for trisomies 21, 18 and 13 in twin pregnancies at 10 + 0 to 14 + 1 weeks' gestation. Two populations were included; first, self-referred women to the Feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 30 publications
8
89
2
Order By: Relevance
“…Xu et al reported that the sensitivity and specificity were 0.9896 and 0.9997 for detection of trisomy 21, 1.00 and 0.9997 for trisomy 18, and 1.00 and 0.9997 for trisomy 13, respectively, in a multicenter follow‐up study of 31 515 singleton pregnancies in southeastern China 39 . All of the above data suggest that the performance of NIPT for trisomy 21 in twin pregnancies was similar to that in singleton pregnancies, as also reported by Nicolaides et al 38 Nicolaides et al mainly compared the pooled weighted detection rate (DR) and false‐positive rate, whereas we mainly analyzed the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and AUC. What is more, we conducted a subgroup analysis to enrich our content.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Xu et al reported that the sensitivity and specificity were 0.9896 and 0.9997 for detection of trisomy 21, 1.00 and 0.9997 for trisomy 18, and 1.00 and 0.9997 for trisomy 13, respectively, in a multicenter follow‐up study of 31 515 singleton pregnancies in southeastern China 39 . All of the above data suggest that the performance of NIPT for trisomy 21 in twin pregnancies was similar to that in singleton pregnancies, as also reported by Nicolaides et al 38 Nicolaides et al mainly compared the pooled weighted detection rate (DR) and false‐positive rate, whereas we mainly analyzed the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and AUC. What is more, we conducted a subgroup analysis to enrich our content.…”
Section: Discussionsupporting
confidence: 83%
“…Thus 32 studies remained to be assessed for eligibility by reading of the full text. Eventually, 21 relevant studies met all the inclusion criteria and were included in this meta‐analysis 9,19‐38 . A flow chart summarizing the selected eligible studies in systematic review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vanishing-twin pregnancies with a CRL measurement of the dead embryo, the mean log 10 MoM was assumed to depend linearly on time since demise; this linear relationship was assumed to continue until the mean log 10 MoM equaled that in vanishing-twin pregnancies with an empty sac. Beyond this, the mean was taken to be constant at this value for all vanishing twins.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity is reduced by 9% for trisomy 21 (T21), 28% for trisomy 18 (T18), and 22% for trisomy 13 (T13) in twin pregnancies compared with those in singleton pregnancies . Very recently, a study showed that the performance of NIPT for T21 in twin pregnancy is similar to that reported in singleton pregnancy, with the sensitivity of 98.2% (95% CI, 83.2%‐99.8%) . Due to the lack of sufficient validation data of the test specificity and sensitivity, NIPT is recommended with caution for twin pregnancies and is not recommended for higher‐order multiple pregnancies .…”
Section: Introductionmentioning
confidence: 99%